Nitric oxide synthase in macula densa regulates glomerular capillary pressure. - Wilcox, C S (1992)
Tubular-fluid reabsorption by specialized cells of the nephron at the junction of the ascending limb of the loop of Henle and the distal convoluted tubule, termed the macula densa, releases compounds causing vasoconstriction of the adjacent afferent arteriole. Activation of this tubuloglomerular feedback response reduces glomerular capillary pressure of the nephron and, hence, the glomerular filtration rate. The tubuloglomerular feedback response functions in a negative-feedback mode to relate glomerular capillary pressure to tubular-fluid delivery and reabsorption. This system has been implicated in renal autoregulation, renin release, and longterm body fluid and blood-pressure homeostasis. Here we report that arginine-derived nitric oxide, generated in the macula densa, is an additional intercellular signaling molecule that is released during tubular-fluid reabsorption and counters the vasoconstriction of the afferent arteriole. Antibody to rat cerebellar constitutive nitric oxide synthase stained rat macula densa cells specifically. Microperfusion of the macula densa segment of single nephrons with N omega-methyl-L-arginine (an inhibitor of nitric oxide synthase) or with pyocyanin (a lipid-soluble inhibitor of endothelium-derived relaxation factor) showed that generation of nitric oxide can vasodilate the afferent arteriole and increase glomerular capillary pressure; this effect was blocked by drugs that prevent tubular-fluid reabsorption. We conclude that nitric oxide synthase in macula densa cells is activated by tubular-fluid reabsorption and mediates a vasodilating component to the tubuloglomerular feedback response. These findings imply a role for arginine-derived nitric oxide in body fluid-volume and blood-pressure homeostasis, in addition to its established roles in modulation of vascular tone by the endothelium and in neurotransmission.